Addressing inequities in headache care by embedding services in a community health center in Boston, MA. Issue 10 (2nd November 2022) - Vgontzas, Angeliki; Loder, Elizabeth
Abstract: There is a critical need to diagnose and treat headache disorders in primary care settings. This is especially true for those who face systemic barriers to healthcare access due to racism or poverty. In order to target those at higher risk of disability associated with neurologic disease in our healthcare system, we embedded a specialized headache and neurology clinic within the Brigham and Women's Hospital Southern Jamaica Plain Community Health Center in Boston, MA. The goal was to create a sustainable, integrated clinic consistent with the CHC's racial justice mission, with an emphasis on equitable care, awareness of structural barriers to care, improved communication with primary care and inclusion of trainees as important members of a healthcare team. In its' first year, the clinic had over 400 patient visits, with a near‐perfect rate of completion of consults. In addition to improved access to tertiary care headache services, successes have included improving continuity of care, cultivating a model of shared care with primary care practitioners and stimulating interest in headache medicine among staff and trainees. Challenges have included the use of staff time to complete prior authorizations, and the need to find or develop Spanish‐language and culturally appropriate patient educational resources. By providing care within the patient's medical home, the headache specialist gains a deeper appreciation of a patient's social determinants of health and can readily access resources to navigate barriers. The personal and professional fulfillment that headache specialists may experience while doing this important work could help protect against burnout. Sustainability depends on ensuring equitable provider reimbursement; departmental and institutional support is essential. We believe this clinic can serve as a model for specialists throughout the United States who wish to improve the delivery of care to patient populations who face access barriers.